2003
DOI: 10.1017/s0954102003001263
|View full text |Cite
|
Sign up to set email alerts
|

Glacial sediment provenance, dispersal and deposition, Vestfold Hills, East Antarctica

Abstract: Abstract:Field observations involving landform evaluation and the physical characterization of sediments, combined with a detailed analysis of the spatial distribution of bedrock and sediment geochemical patterns, suggests a limit to the glacial transport half-distance of c. 3 km in Vestfold Hills. Four morphologically distinct glacial deposits were sampled (small debris ridges, large debris ridges, debris drapes and valley fills) on the basis of field geometry. These landforms were subsequently distinguished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…The variation in sorting at local scale in a limited area is well reported from Vestfold Hills, East Antarctica due to winnowing of fine grained lighter and platy minerals by melt water causing local textural variations (Gore et al 2003). The plot of skewness vs. kurtosis (Fig.5F) shows a wide range of platykurtic, mesokurtic and leptokurtic sediments, however, dominantly restricted in near-symmetrical to fine-skewed category.…”
Section: Bivariate Plotssupporting
confidence: 65%
“…The variation in sorting at local scale in a limited area is well reported from Vestfold Hills, East Antarctica due to winnowing of fine grained lighter and platy minerals by melt water causing local textural variations (Gore et al 2003). The plot of skewness vs. kurtosis (Fig.5F) shows a wide range of platykurtic, mesokurtic and leptokurtic sediments, however, dominantly restricted in near-symmetrical to fine-skewed category.…”
Section: Bivariate Plotssupporting
confidence: 65%
“…In the south-eastern part of the area, limited areas rise to about 15 m.a.s.l. At the southern margin, the land rises steeply to 10 m to an ice-cored moraine described by Adamson & Pickard (1986b), Fitzsimons (1997) and Gore et al (2003). There is no marked general slope as would be expected if isostasy and glacial retreat were active over a long time interval.…”
Section: Marine Plain Surfacementioning
confidence: 92%
“…This block forms an elevated plateau surrounded by deep troughs to the south and west, and probably deeper but more gently sloping bedrock to the north and east, though information on subice topography in these areas is limited. The Cenozoic geology and geomorphology of the Vestfold Hills have been extensively studied (Pickard 1982, Adamson & Pickard 1986a, 1986b, Fitzsimmons 1991, 1996, Gore et al 2003, Quilty 2006. The overall picture is one of east-west to WSW-ENE trending valleys, floored with sediments and containing lakes.…”
Section: Study Areamentioning
confidence: 99%
“…Biogenic silica and carbonate content data was also available for 20 of these samples. Data on gravelsand-mud content of onshore deposits collected by sieve analysis are available in a number of published papers (Hirvas et al 1993, Gore et al 2003, Colhoun et al 2010 and an unpublished soil survey by Makarucha (1984). The locations of all sediment samples used in this study are shown in Fig.…”
Section: Sediment Samplingmentioning
confidence: 99%